Application of Fatigue Simulation Analysis Based on CDTire. Issue 1 (October 2020) - Tang, Yan; Xiaobing, Bu; Fengling, Gao; Bayi, Yu; Dongliang, Geng; Yuan, Wu
Abstract: In order to verify the fatigue-durability performance of chassis components, the simulation and analysis process is established in this paper based on CDTire model. High-accuracy tire model is constructed by CDTire modeling software according to the tire test data. The multi-body dynamics simulation is completed by combining the CDTire model with the vehicle model. The load of chassis components is extracted and imported into fatigue software. The swing arm is taken as an example for calculation. This analysis process can guide the analysis of chassis components and shorten the development cycle.